How do differences in Achilles’ tendon moment arm lengths affect muscle-tendon dynamics and energy cost during running? - Bennett, Eric C.; Machado, Esthevan; Fletcher, Jared R. (Frontiers in Sports and Active Living, 2023)
The relationship between the Achilles tendon moment arm length (ATMA) and the energy cost of running (Erun) has been disputed. Some studies suggest a short ATMA reduces Erun while others claim a long ATMA reduces Erun. For a given ankle joint moment, a short ATMA permits a higher tendon strain energy storage, whereas a long ATMA reduces muscle fascicle force and shortening, and thereby muscle energy cost. Both are potential conflicting mechanisms to reduce Erun, since AT energy storage comes at a metabolic cost. Neither of these proposed mechanisms have been examined together. We measured ATMA using the tendon travel method in 17 males and 3 females (24±3 years, 75±11 kg, 177±7 cm). They ran on a motorized treadmill for 10 mins at 2.5 m⸱s-1 while Erun was measured. AT strain energy storage, muscle lengths, velocities and muscle energy cost were calculated during time-normalized stance from force and ultrasound data. A short (SHORT n=11, ATMA=29.5±2.0 mm) and long (LONG, n=9, ATMA=36.6±2.5 mm) ATMA group was considered based on a bimodal distribution of measured ATMA. Mean Erun was 4.9±0.4 J⸱kg-1⸱m-1. The relationship between ATMA and Erun was not significant (r2=0.13, p=0.12). Maximum AT force during stance was significantly lower in LONG (5819±1202 N) compared to SHORT (6990±920 N, p=0.028). Neither AT stretch nor AT strain energy storage was different between groups (mean difference: 0.3±1 J⸱step-1, p=0.84). Fascicle force was significantly higher in SHORT (508±93 N) compared to LONG (468±84 N. p=0.02). Fascicle lengths and velocities were similar between groups (p>0.72). Muscle energy cost was significantly lower in LONG (0.028±0.08 J⸱kg⸱step-1) compared to SHORT (0.045±0.14 J⸱kg⸱step-1 p=0.004). There was a significant negative relationship between ATMA and total muscle energy cost relative to body mass (r=-0.699, p<0.001). Together these results suggest that a LONG ATMA serves to potentially reduce Erun by reducing the muscle energy cost of the plantarflexors during stance. The relative importance of AT energy storage and return in reducing Erun should be re-considered.